The experiential ontology of Hannah Arendt - Maslin, Kimberly (Lexington Books, 2020)
Intro -- Title Page -- Introduction -- Heidegger the Fox -- Rootlessness in Heidegger and Arendt -- Concretizing Thrownness and Projection -- MitDasein I -- Mitdasein II -- Vorspringen (Leaping Ahead) -- On the Political Importance of a Normative Ontology -- The Politics of Existential Loneliness -- Experiential Ontology -- Theorizing #MeToo -- Conclusion -- Bibliography -- Index -- About the Author